K-9 national park defenders - Lee, Katy; Stover, Sharee (Love inspired suspense., 2023)
A Christmas skiing retreat turns treacherous when Pacific Northwest K-9 Unit officer Veronica Eastwood's sister is kidnapped--and only rival officer Parker Walsh can help her in Katy Lee's Yuletide Ransom. And in Sharee Stover's explosive Holiday Rescue Countdown, K-9 officers Dylan Jeong and Brandie Weller must race against the clock when they face a Christmas parade bomb threat...and a killer from Dylan's past.